The four worlds of ‘welfare reality’ – social risks and outcomes in Europe - Ferragina, E; Seeleib-Kaiser, M; Spreckelsen, T (Cambridge University Press, 2014)
After three decades of welfare state crisis, change and transformation can we still speak of welfare state regimes when looking at their outcomes? The analysis of outcomes provides a picture of ‘the real worlds of welfare’ and is of considerable importance to understanding political legitimacy across countries. We use aggregate longitudinal data for West European countries in order to map welfare outcomes and cluster countries. The cluster results are also assessed for their sensitivity to the choice of different countries, years or indicators. All European welfare states have a significant capacity for reducing poverty and inequality. However, the degree of this reduction varies considerably, especially when examining different social groups, i.e. unemployed people, children, youths or the elderly. Outcomes cluster countries largely in line with previous institutionalist literature, differentiating between conservative, liberal, Mediterranean and social-democratic regimes. As the main exception, we identify Germany, which can no longer be characterised as the proto-typical conservative welfare state. When analysing old social risks such as unemployment and old age, Europe appears to be characterised by two groups, i.e. one consisting of liberal and Mediterranean countries and a second made up of social-democratic and conservative countries. New social risks such as child and youth poverty, by contrast, replicate very closely the theoretical four-cluster typology. Our sensitivity analyses reveal that our clusters tend to be stable over time. Welfare regimes continue to serve as a useful analytical tool and relate to outcomes experienced by European citizens.